EFEKTIVITAS PENGGUNAAN VIDIO PEMBELAJARAN BERBASIS FILM KARTUN UNTUK MENINGKATKAN KEMAMPUAN ISTIMA’ (MENYIMAK) BAHASA ARAB SISWA KELAS III MI ASSEGAF PALEMBANG - Dea Sri Maharani; Yuniar; Qoim Nurani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2026)
This study was motivated by the low Arabic listening (istimā’) ability of third-grade students at MI Assegaf Palembang, which was reflected in their difficulties in understanding vocabulary, pronunciation, and basic conversational meaning. This research aims to determine the effectiveness of using cartoon-based instructional videos to improve students’ listening skills. A quantitative method with a quasi-experimental One Group Pretest–Posttest design was employed. The sample consisted of 23 students, and the data were collected through pretests, posttests, classroom observations, and documentation, then analyzed using the Wilcoxon Signed Ranks Test. The results indicate a significant improvement in students’ listening ability, as shown by the increase in the average score from 48.70 on the pretest to 67.52 on the posttest. The Wilcoxon test yielded a significance value of 0.000 (<0.05), confirming that cartoon-based videos are effective in enhancing Arabic listening skills. These findings imply that engaging audio-visual media aligned with the cognitive characteristics of elementary learners can effectively increase motivation, attention, and comprehension in Arabic language learning. Keywords: Instructional Video; Cartoon Film; Istimā’ Skill; Arabic Listening